Diseño de un DVD multimedia interactivo con la promoción turística del cantón Píllaro provincia de Tungurahua - Pilapanta Lucero, Danilo Fabián (2014)
The present proyect proposed the design of an interactive multimedia DVD with the tourist promotion of the Canton Píllaro for the which have used actuality computing of the tecnology for the creation of the graphic piece.Within the application incorporating multimedia elements that are justified by use and evidence. In developing the proposal seeks to capture the attention of the user or visitor using creative ideas through graphic design, medium what search consolidate essential a work of quality to the citizens of Canton Píllaro. In the process of formulating the theoretical distribution is shown in three chapters, the first chapter deals with basic aspects of design and multimedia, same what are grounded with an appropriate bibliography and actuality. The second chapter supports the project through the application of citizen surveys and interviews with authorities of Píllaro, which are included directly and indirectly in the proposed projecting favorable results. In definitive, the third chapter is about the development of interactive multimedia application which contains detailed logical design process, layout and animation of objects up to an interactive application.